ON THE STABILITY CONDITIONS OF 2D TIME FRACTIONAL DIFFUSION EQUATION - Adel Rashed A. Ali Alsabbagh; Esraa Abbas Al-taai (Al-Qadisiyah Journal of Pure Science, 2020)
The Caputo definition of fractional derivative has been employed for the time derivative for the two-dimensional time-fractional diffusion equation. The stability condition obtained by reformulation the classical multilevel technique on the finite difference scheme. A numerical example gives a good agreement with the theoretical result